REVIEW OF THE EFFECT OF INDUSTRIAL WASTE ON SELF COMPACTING CONCRETE - Tengku Alif Rafli Mosyani; Lisa Oksri Nelfia; Agung Sumarno (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2023)
Self-Compacting Concrete (SCC) is an innovation in concrete technology used in building elements with dense and complex reinforcement frameworks. SCC is characterized by its high fluidity and the ability to self-compact without the use of vibrators. Superplasticizer is one of the components applied in the production of SCC. The use of superplasticizer aims to reduce water consumption, accelerate the setting time, improve concrete workability, and also make the concrete impermeable. As time progresses, industrial waste continues to increase, highlighting the importance of recycling industrial waste. The purpose of this research is to investigate the influence of industrial waste as a substitute material for fine aggregates on the workability and compressive strength of SCC. This study is the result of a literature review obtained by examining various sources including books, proceedings, as well as international and national journals. The results of this literature study involve the use of industrial waste materials such as recycled glass, granite waste, nickel slag, and copper slag as substitutes for fine aggregates. The results of the workability and compressive strength of SCC are influenced by the characteristics of each industrial waste used. This indicates an improvement in the flowability (slump flow) with an increasing percentage of industrial waste, ranging from 0% to 60%, in the concrete composition. Compressive strength test results indicate that the optimal percentage of industrial waste addition in the concrete composition lies between 20% and 40%.